Dietary patterns are associated with improved ovarian reserve in overweight and obese women: a cross-sectional study of the Lifestyle and Ovarian Reserve (LORe) cohort - Ashley M. Eskew; Bronwyn S. Bedrick; Jorge E. Chavarro; Joan K. Riley; Emily S. Jungheim (BMC, 2022)
Abstract Background Growing evidence suggests that adherence to certain dietary patterns is associated with improved fecundity and reproductive outcomes in the general population and infertile couples assisted reproductive treatments. The objective of this study was to assess if dietary patterns are associated with ovarian reserve in reproductive age women without a history of infertility. Methods This was a cross-sectional study of 185 women in the Lifestyle and Ovarian Reserve (LORe) cohort. Women aged 18-44 without a history of infertility were recruited from the local community at an academic medical center. Subjects completed validated food frequency and physical activity questionnaires to assess patterns over the year prior to presentation. Dietary patterns including a Western (including meat, refined carbohydrates, high-calorie drinks), prudent (including fruits, vegetables, olive oil and nuts), fertility (lower intake of trans fat with higher intake of monounsaturated fatty acids, increased intake of plant based protein, high-fat dairy, lower glycemic load carbohydrates and supplemental iron) and profertility diet (PFD) (characterize by whole grains, soy and seafood, low pesticide residue produce, supplemental folic acid, B12 and vitamin D) were identified through principal component analysis. Main outcome measures were serum antimullerian hormone concentration (AMH) (ng/mL) and antral follicle count (AFC) obtained by transvaginal ultrasound. Results After stratifying by BMI, adjusting for age, smoking and physical activity, dietary patterns were not associated with ovarian reserve in normal weight women. Increased adherence to a profertility diet in overweight and obese women (BMI ≥ 25 kg/m2) was associated with a significantly higher AMH. Women in the third and fourth quartiles of PFD adherence had a mean AMH concentration of 1.45 ng/mL (95%CI 0.33-2.56, p = 0.01) and 1.67 ng/mL (95%CI 0.60-2.74, p = 0.003) higher than women in the lowest quartile respectively. The highest adherence to PFD was also associated with a higher AFC in women with a BMI ≥ 25 kg/m2 (β = 7.8, 95%CI 0.003-15.34, p < 0.05). Other common dietary patterns were not significantly associated with ovarian reserve. Conclusions Increased adherence to a profertility diet is associated with improved markers of ovarian reserve in overweight and obese women. These findings provide novel insight on potential modifiable lifestyle factors associated with ovarian reserve.